José Antonio de Soto Saldaña. Vida y lectura de un conspirador - Guzmán Pérez, Moisés (El Colegio de México, A.C., 2011)
By resorting to the life of José Antoniode SotoSaldaña, one of the participants in the conspiracy of Valladolid in 1809, this essay seeks to examine the political culture characterizing one group of the Novohispanic society in transition. This society was strongly based on tradition and religious values, certainly learned and at the same time renewed with the ideas of liberalism and modern philosophy. The analysis of Soto Saldaña’s library, the richest and largest library owned by a layman in the diocese of Michoacán at that moment; the reading of newspapers, booklets or political pamphlets, as well as the changes that took place in the sociability and reading practices of the age, are closely related to a political conspiracy whose participants posited a peculiar independence project to face the political crisis caused by the abdications of the royal family at Bayona.